Manual proposal to audit the automated accounting system in accordance with the framework (COBIT): Applied Research in the General Company for Petrochemical Industries (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The information revolution، the new language has become one for all the peoples of the world through handling and exchange and to participate in all key areas (economic، cultural and scientific) and Accounting episode of this revolution has turned most of the traditional systems (manual) in companies to automated systems، this transformation in the regulations summoned from the auditors that develops their traditional examination automated systems so had to provide tools for auditing help auditors to keep abreast of developments and as a result there is no evidence checksum Local Private audited automated systems came search to provide evidence helps auditors for guidance as part of COBIT، which provides audit procedures Detailed information technology and private accounting information systems automated.The research aims to propose the Local Audit Manual to audit automated accounting systems